PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS PASIEN PENGGUNA BPJS DENGAN KEPUASAN PASIEN SEBAGAI VARIABEL INTERVENING DI POLIKLINIK RAWAT JALAN RSUI BANYU BENING BOYOLALI - Sutanto, Heri; Suddin, Alwi; Sriwidodo, Untung (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2019)
This study analyzed the impact of service quality on loyalty through satisfaction of patients on BPJS in Inpatient Hospital Banyu Bening Boyolali.. The purpose of this study was to analyze the impact of service quality on patient loyalty, analyze the influence of service quality on patient satisfaction, patient satisfaction to analyze the effect of patient loyalty, and analyze the impact of service quality on loyalty indirectly through patient satisfaction in patients on inpatient BPJS Hospital Banyu Bening Boyolali.. This type of research used in this study is descriptive and analytical. The samples in this study were 100 patients BPJS users in inpatient wards in hospitals Banyu Bening Boyolali. This study used path analysis techniques. The results of this study that the quality of service has an influence on patient loyalty, service quality has an influence on patient satisfaction, patient satisfaction has an influence on patient loyalty, and service quality has an indirect effect on patient loyalty through patient satisfaction.